Increased appendicularian zooplankton alter carbon cycling under warmer more acidified ocean conditions. (29th March 2017) - Winder, Monika; Bouquet, Jean‐Marie; Rafael Bermúdez, J.; Berger, Stella A.; Hansen, Thomas; Brandes, Jay; Sazhin, Andrey F.; Nejstgaard, Jens C.; Båmstedt, Ulf; Jakobsen, Hans H.; Dutz, Jörg; Frischer, Marc E.; et al.
Abstract: Anthropogenic atmospheric loading of CO2 raises concerns about combined effects of increasing ocean temperature and acidification, on biological processes. In particular, the response of appendicularian zooplankton to climate change may have significant ecosystem implications as they can alter biogeochemical cycling compared to classical copepod dominated food webs. However, the response of appendicularians to multiple climate drivers and effect on carbon cycling are still not well understood. Here, we investigated how gelatinous zooplankton (appendicularians) affect carbon cycling of marine food webs under conditions predicted by future climate scenarios. Appendicularians performed well in warmer conditions and benefited from low pH levels, which in turn altered the direction of carbon flow. Increased appendicularians removed particles from the water column that might otherwise nourish copepods by increasing carbon transport to depth from continuous discarding of filtration houses and fecal pellets. This helps to remove CO2 from the atmosphere, and may also have fisheries implications.